Playing stereoscopic video games enhances the precision but not the accuracy of depth perception - Roger W. Li; Betty Z. Li; Sandy W. Chat; Dennis M. Levi (Scientific Reports)
Abstract Playing three-dimensional (3D) video games enhances stereo acuity (i.e., the precision of stereopsis) in young adults with normal vision Here we asked whether the improvement in stereoacuity was the result of a reduced disparity pedestal, as indicated by a decreased subjective depth bias (i.e., the accuracy of stereopsis). Twenty-one healthy young participants with normal vision and limited previous video game experience, none had played 3D video games, played first-person-shooter action stereoscopic 3D video games for a total of 40 h. Depth detection performance was measured using random dot stereograms before and after the video game intervention. We found that playing stereoscopic 3D video games boosts the precision, but not the accuracy of depth perception, suggesting that the enhanced stereoacuity did not result from reducing the effects of a disparity pedestal. These types of video games have potential therapeutic applications for improving stereo vision in patients with binocular vision anomalies.